PENINGKATAN HASIL BELAJAR MATA PELAJARAN PENDIDIKAN PANCASILA MATERI NORMA DALAM KEHIDUPANKU MELALUI MODEL PROJECT BASED LEARNING PADA SISWA KELAS V - Nuraeni Tagos; Mujahid Damopolii; Aris Iskandar (Al-mujahidah, 2026)
This study aims to apply the Project Based Learning model in class V of SDN 9 Limboto to improve student learning outcomes on the topic "Norms in My Life." The main problem faced is the low level of student understanding due to the use of less interesting learning methods, which makes students tend to be passive. To overcome this, the Project Based Learning model is used which encourages students to be more active in discovering and understanding the material through an exploration process. The method used in this study is Classroom Action Research (CAR) which is implemented in two cycles. Each cycle includes the stages of planning, action implementation, observation, and reflection. Data collection techniques include observation, testing, and documentation. The results of the study show that in the pre-cycle stage only 20% of students achieved the Learning Objective Achievement Criteria (KKTP). After the implementation of the project based learning model, in the first cycle the student's score increased to 60% with a student completion rate of . In the second cycle, there was another significant increase to 87%, with 13 students having achieved KKTP. These findings indicate that the project based learning model is effective in improving student learning outcomes on the material norms in my life.